PENANAMAN NILAI-NILAI KARAKTER SISWA DALAM UPAYA PENCEGAHAN TERJADINYA 3 DOSA BESAR DUNIA PENDIDIKAN - Rafika Nuriafuri; Dini Rakhmawati; Arry Handayani (STKIP Subang, 2024)
Particularly in the field of education, character education is still severely inadequate today. The crimes perpetrated by primary school pupils, who are often more impacted by cognitive and contextual factors than their character development, demonstrate the lack of character education. There's a lot of nasty conduct going on these days. It has recently come to light that there are